2023
DOI: 10.1111/iwj.14263
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of procalcitonin and red blood cell distribution width at admission on the prognosis of patients with severe burns: A retrospective analysis

Abstract: The plasma procalcitonin (PCT) concentration and red blood cell distribution (RDW) value after severe burns can be used as prognostic indicators, but at present, it is difficult to give consideration to sensitivity and specificity in diagnosing the prognosis of severe burns with a single indicator. This study analysed the diagnostic value of plasma PCT concentration and RDW value at admission on the prognosis of severe burn patients to improve its sensitivity and specificity. A total of 205 patients with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A retrospective study by Qiu et al [ 24 ] reported that the cut-off points of RDW were 13.5 for the 3rd day and 13.6 for the 7th day postburn. In another study with 205 patients, Tang et al [ 25 ] demonstrated that RDW showed a cut-off point of 14.55. Also, a very recent study showed a value of 13.05 for 30-day postburn mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Qiu et al [ 24 ] reported that the cut-off points of RDW were 13.5 for the 3rd day and 13.6 for the 7th day postburn. In another study with 205 patients, Tang et al [ 25 ] demonstrated that RDW showed a cut-off point of 14.55. Also, a very recent study showed a value of 13.05 for 30-day postburn mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%